2014
DOI: 10.1016/j.resuscitation.2013.08.275
|View full text |Cite
|
Sign up to set email alerts
|

A history of smoking is associated with improved survival in patients treated with mild therapeutic hypothermia following cardiac arrest

Abstract: Objectives To assess the association between smoking and survival with a good neurologic outcome in patients following cardiac arrest treated with mild therapeutic hypothermia (TH). Methods We conducted a retrospective observational study of a prospectively collected cohort of 188 consecutive patients following cardiac arrest treated with TH between May 2007 and January 2012. Smoking status was retrospectively collected via chart review and was classified as “ever” or “never”. Primary endpoint was survival t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The association between smoking and favorable outcomes has been reported previously, and has been postulated to reflect preconditioning as a result of low level carbon monoxide exposure. 26 An alternative possibility is that smoking results in CAD making smokers more likely to have cardiac etiology arrest which is associated with better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The association between smoking and favorable outcomes has been reported previously, and has been postulated to reflect preconditioning as a result of low level carbon monoxide exposure. 26 An alternative possibility is that smoking results in CAD making smokers more likely to have cardiac etiology arrest which is associated with better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…15 Our findings are similar to studies investigating mortality outcomes in patients hospitalized for acute cardiac events, including cardiac arrest. [6][7][8] Although the etiology of the beneficial effect of smoking is unknown, it is possible that physiological changes associated with smoking or some component of tobacco smoke is protective during an ischemic event which can be brought on by injury, stroke, cardiac arrest, or heart attack. 7,22 For each of these conditions, with the exception of injury, current smokers were reported to have reduced in-hospital mortality by at least one study.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Although the etiology of the beneficial effect of smoking is unknown, it is possible that physiological changes associated with smoking or some component of tobacco smoke is protective during an ischemic event which can be brought on by injury, stroke, cardiac arrest, or heart attack. 7,22 For each of these conditions, with the exception of injury, current smokers were reported to have reduced in-hospital mortality by at least one study. 1,5,6 This is the first report of the smoker's paradox in the injured patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple preclinical studies confirmed the paradoxical effect of smoke on mortality after MI and attributed the beneficial effects to cardiac gap junction remodeling and preconditioning [ 27 , 112 ]. Smoking was independently associated with improved survival in patients with cardiac arrest and lower inpatient mortality in acute ischemic stroke and STEMI [ 107 , 110 , 111 ]. Results were attributed in part to changes in vascular reactivity due to a global smoking-induced ischemic conditioning.…”
Section: The Smoker's Paradoxmentioning
confidence: 99%